FAKTOR KEPEMIMPINAN DAN KOMPENSASI DALAM PENGUKURAN LOYALITAS PEGAWAI - Batubara, Soulthan Saladin; Matondang, Edi Saputra; Satria, Bima (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
Employee work loyalty can be understood as affective commitment among employees. To be able to increase loyalty, organizations are required to develop, and manage their human resources to be able to work professionally. This human resource management really needs support from top management as the first step. In addition, employees who get compensation that meets their living needs will tend to be more loyal to the company. This study was conducted to see the influence of leadership and compensation on employee loyalty of the Binjai City Transportation Office. This study used an associative approach with a correlational analytic design. Data is collected through questionnaires, interviews and documentation studies. Questionnaires are calculated with likert scale measurement units, and processed using the SPSS (statistical product and service solution) program The results of the study showed that both partially and simultaneously the variable of leadership and compensation had a positive and significant effect on employee loyalty.